Closed occlusion due to colon cancer left. Experience on resection and anastomosis at one time - Torres, Marcos; González, Daniel; di Leoni, Francisco; Vega, Alvaro; Monti, José; Amorín, Raúl (Cirugía del Uruguay, 2003)
Review of the authors' experience in the management of occ!usions due to left colony cancer, during the period between 1993 through 1999, in the city ofFlorida, Uruguay. Eighteen procedures were carried out: in 16 cases tumor was resected; in 15 patients transit of intestine was restored in the same surgical act and of these latter, in 11 patients a colocolic anastomosis was performed (77.7% of cases among the 18 patients operated or 87.5% of resected patients). Mortality was no higher than that set forth for other procedures, which are already broadly accepted, and mortality occurred in 3 patients. There was no suspected suture failure in any of the cases